2007
DOI: 10.1145/1276933.1276934
|View full text |Cite
|
Sign up to set email alerts
|

Recovering traceability links in software artifact management systems using information retrieval methods

Abstract: The main drawback of existing software artifact management systems is the lack of automatic or semi-automatic traceability link generation and maintenance. We have improved an artifact management system with a traceability recovery tool based on Latent Semantic Indexing (LSI), an information retrieval technique. We have assessed LSI to identify strengths and limitations of using information retrieval techniques for traceability recovery and devised the need for an incremental approach. The method and the tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
231
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 284 publications
(239 citation statements)
references
References 63 publications
5
231
2
1
Order By: Relevance
“…In consequence, IRRF eliminates the reformulation step and allows developers to focus on what they know best (i.e., source code rather than queries) by reformulating the queries automatically. Earlier work on traceability [7,11] showed that RF improves an IR task, but not in all cases. The goal of our case study was to see if this is true also in the case of concept location, given the fact that the context is different.…”
Section: Case Studymentioning
confidence: 96%
See 2 more Smart Citations
“…In consequence, IRRF eliminates the reformulation step and allows developers to focus on what they know best (i.e., source code rather than queries) by reformulating the queries automatically. Earlier work on traceability [7,11] showed that RF improves an IR task, but not in all cases. The goal of our case study was to see if this is true also in the case of concept location, given the fact that the context is different.…”
Section: Case Studymentioning
confidence: 96%
“…For jEdit 7 and Adempiere 8 , we analyzed the bug tracking systems hosted on the projects' sourceforge.net website. Both projects have systems that keep track of the patches submitted for known bugs in the source code.…”
Section: Data -Software and Change Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…IR-based methods have been applied to support practical tasks. For instance, IR methods have been successfully used to support feature location (Liu et al 2007;Eaddy et al 2008;Revelle and Poshyvanyk 2009;Revelle et al 2010;Dit et al 2012a;Dit et al 2012b;, traceability link recovery (Antoniol et al 2002;Hayes et al 2006;De Lucia et al 2007;Cleland-Huang et al 2010;Oliveto et al 2010;Gethers et al 2011), and impact analysis (Antoniol et al 2000;Canfora and Cerulo 2005;Poshyvanyk et al 2009;Gethers and Poshyvanyk 2010;Gethers et al 2012). We do not discuss other applications of IR-based techniques in the context of software maintenance due to space limitations; however, interested readers are referred to (Binkley and Lawrie 2010a;Binkley and Lawrie 2010b) for such an overview.…”
Section: Conceptual Information In Softwarementioning
confidence: 99%
“…Uncovering traces between requirements documents and source code to ease maintenance has been investigated by Charrada [13], [14]. Lucia et al [15] present an approach and a tool to automatically uncover trace links between a wider range of artifacts, among them use cases. Lormans [16] uses trace link recovery to identify requirements that have not been implemented.…”
Section: Related Workmentioning
confidence: 99%